To solve the equation \(2x - 5 = 3(4x + 5)\), we can follow these steps in the correct order:
-
Step 1: Distributive Property to get: \[ 2x - 5 = 12x + 15 \]
-
Step 2: Addition of Equality Property to get: \[ 2x - 12x = 15 + 5 \quad \text{(adding -12x to both sides and } +5 \text{ to both sides)} \] This simplifies to: \[ -10x = 20 \]
-
Step 3: Division of Equality Property to get: \[ x = -2 \quad \text{(dividing both sides by -10)} \]
Note that the step where you mentioned "Combine Like Terms" isn't necessary in that way, since once \(2x - 12x = 20\) is simplified directly.
So the correct order of steps should be:
- Step 1: Distributive Property
- Step 2: Addition of Equality Property
- Step 3: Combine Like Terms (which occurs in Step 2) but is implied
- Step 4: Division of Equality Property
Final ordered steps:
- Distributive Property to get \(2x - 5 = 12x + 15\)
- Addition of Equality Property to get \(-10x = 20\)
- Division of Equality Property to get \(x = -2\)